Konsep Dan Ciri-ciri Tamadun dalam Al-Qur’an - Mohammad, Ali (Jurnal Usuluddin, 2002)
Islamic civilization is the fruit and result of Islam as a religion. Its development is basically based on the major sources of Islam, i.e. the Qur’an and the Prophetic tradition. This civilization is a universal civilization as Islam is. This article presents the concept and major elements of Islamic civilization based on Qur’anic perspective.